Use of Pyrosequencing and Denaturing Gradient Gel Electrophoresis to Examine the Effects of Probiotics and Essential Oil Blends on Digestive Microflora in Broilers Under Mixed Eimeria Infection - Hume, Michael E.; Barbosa, Nei A. [UNESP]; Dowd, Scot E.; Sakomura, Nilva K. [UNESP]; Nalian, Armen G.; Kley, Alexandra Martynova-Van; Oviedo-Rondon, Edgar O. (Mary Ann Liebert, Inc., 2011)
A protective digestive microflora helps prevent and reduce broiler infection and colonization by enteropathogens. In the current experiment, broilers fed diets supplemented with probiotics and essential oil (EO) blends were infected with a standard mixed Eimeria spp. to determine effects of performance enhancers on ileal and cecal microbial communities (MCs). Eight treatment groups included four controls (uninfected-unmedicated [UU], unmedicated-infected, the antibiotic BMD plus the ionophore Coban as positive control, and the ionophore as negative control), and four treatments (probiotics BC-30 and Calsporin; and EO, Crina Poultry Plus, and Crina PoultryAF). Day-old broilers were raised to 14 days in floor pens on used litter and then were moved to Petersime batteries and inoculated at 15 days with mixed Eimeria spp. Ileal and cecal samples were collected at 14 days and 7 days postinfection. Digesta DNA was subjected to pyrosequencing for sequencing of individual cecal bacteria and denaturing gradient gel electrophoresis (DGGE) for determination of changes in ileal and cecal MC according to percentage similarity coefficient (%SC). Pyrosequencing is very sensitive detecting shifts in individual bacterial sequences, whereas DGGE is able to detect gross shifts in entire MC. These combined techniques offer versatility toward identifying feed additive and mild Eimeria infection modulation of broiler MC. Pyrosequencing detected 147 bacterial species sequences. Additionally, pyrosequencing revealed the presence of relatively low levels of the potential human enteropathogens Campylobacter sp. and four Shigella spp. as well as the potential poultry pathogen Clostridiun perfringens. Pre- and postinfection changes in ileal (56%SC) and cecal (78.5%SC) DGGE profiles resulted from the coccidia infection and with increased broiler age. Probiotics and EO changed MC from those seen in UU ilea and ceca. Results potentially reflect the performance enhancement above expectations in comparison to broilers not given the probiotics or the specific EO blends as feed supplements.